International Visegrad project: possibilities and barriers for industry 4.0 implementation in SMEs in V4 countries and Serbia (Serbian Journal of Management, 2022)
This issue of Serbian Journal of Management (SJM 17(1) 2021), is dedicated to digitalisation of the small and medium sized enterprises through contemporary concept of Industry 4.0. Accordingly, the articles published in this issue are all dealing with the different aspects of digitalisation of the business processes, methods and tools consisted in the Industry 4.0 paradigm and their utilisation in the everyday practice of the SMEs. Part of the articles published in this issue are directly presenting the results of the project: Possibilities and barriers for Industry 4.0 implementation in SMEs in V4 countries and Serbia, which was financially supported by the International Visegrad Fund, under the grant number: 22110036. In frame of the project, research group consisted fro scholars from all four Visegrad group countries, as well as researchers from Serbia, have prepared the measuring scale - questionnaire to assess the level of digitalisation of the SMEs in their region. Also, they assessed the entrepreneurs opinion on the Industry 4.0 and its applicability in their business operations. The main purpose of this investigation was to identify both possibilities and the barriers for I 4.0 implementation at the SMEs level. Obtained results of this research are presented in part of the manuscripts published in this issue. Also, part of the manuscripts in this issue are invited from the authors who are also investigating in the field of digitalisation and Industry 4.0, but are not included in the mentioned project.
Keywords: International Visegrad Fund; Industry 4.0; digitalisation